PENGARUH DIGITAL MARKETING TERHADAP CUSTOMER RETENTION DENGAN CUSTOMER ENGAGEMENT SEBAGAI VARIABEL MEDIASI PADA PRODUK CLOTHING LINE ERIGO DI KOTA MALANG - Dwi Danesty Deccasari; Gredy Yudha Ardian (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
The purpose of this study is to analyze the influence of digital marketing on customer retention with customer engagement as a mediating variable on Erigo clothing line products in Malang City. This research method uses quantitative. The population of the study is Erigo Generation Z consumers aged (14-27 years) who use social media in Malang City. The research sample uses the Lemeshow formula totaling 100 people. The test tool uses Path Analysis. The results of the study indicate that digital marketing has a significant effect on customer retention decisions at Erigo Clothing Line Malang. Customer Engagement has a significant effect on customer retention decisions at Erigo Clothing Line Malang. Customer Engagement can mediate the influence of digital marketing on customer retention decisions at Erigo Clothing Line Malang.